PELANGI: INOVASI PELAYANAN AKTA KELAHIRAN DI KOTA BANDA ACEH - Zamharira, Cut; Cahyani, Indah Rita (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
One form of bureaucratic reform in public services is to bring innovation. Since 2015 the city of Banda Aceh has implemented innovations in birth certificate services, by presenting PELANGI (direct servants). Pelangi is a mechanism for making birth certificates based on a mobile car with a proactive system. Department of Population and Civil Registration of the city of Banda Aceh visited villages in Banda Aceh City and provided birth certificate registration services on-site. The purpose of this study was to find out how the implementation of the